1985
DOI: 10.1002/ajh.2830190308
|View full text |Cite
|
Sign up to set email alerts
|

Lupus anticoagulant: An analysis of the clinical and laboratory features of 219 cases

Abstract: To define clinical and laboratory characteristics of the lupus anticoagulant (LA), we reviewed our experience (219 subjects). Subjects were divided into group A, those with the LA and the diagnosis of lupus erythematosus, group B, those with the LA but nonlupus diagnoses, and group C, those with drug-related lupus syndromes. The typical laboratory findings consisted of a prolonged and inhibited plasma clot time (an average of 1.9 times control time) which was proportionately more prolonged than the partial thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
99
2
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(109 citation statements)
references
References 37 publications
(20 reference statements)
7
99
2
1
Order By: Relevance
“…It has been reported that LA does not prolong PT due to a high concentration of phospholipid in the thromboplastin reagent [23]. APTT is a common screening test for LA though it is reported to be insufficiently sensitive [24]. In the present study 3 of 8 (18.7 %) patients with prolonged APTT were confirmed to be LA positive.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that LA does not prolong PT due to a high concentration of phospholipid in the thromboplastin reagent [23]. APTT is a common screening test for LA though it is reported to be insufficiently sensitive [24]. In the present study 3 of 8 (18.7 %) patients with prolonged APTT were confirmed to be LA positive.…”
Section: Discussionsupporting
confidence: 47%
“…[2][3][4] The mechanism of the characteristic prothrombotic state related to aPLs during APS is still under debate. 5 Much of it is related to the definition of the precise nature of aPL specificity, which remains unclear because of the number of possible antigenic targets discovered over the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism is the most common clinical presentation of APS, occurring in 30-70% of patients 3 . In relation to arteries, the carotid arteries are the main affected vessels and their thrombi may develop into a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac alterations are frequently observed, especially valvular heart disease (thickening and vegetations) and coronary artery disease (CAD) [2][3][4] ; the presence of thrombi has been also reported 5 . However, myocardial involvement is rarely described in this pathology 6 .…”
Section: Introductionmentioning
confidence: 99%